Peroxydisulfate Co-Treatment with MnOx-Loaded Biochar for COD Removal from Automobile Service Station Wastewater - Glinsukol Suwannarat; Kunlasatree Pattanagulanan; Chonlada Rueangsukhon; Panatda Nasingthong; Chompoonut Chaiyaraksa (Current Applied Science and Technology, 2022)
This research was aimed at recycling agricultural waste and treating synthetic automobile service station wastewater. Wastewater was synthesized to two levels of COD concentration: 702 mg/L (WW-A) and 7,054 mg/L (WW-B). In the treatment process, 100 mM sodium peroxydisulfate with MnOx-loaded biochar (MnOx-Biochar) was applied. The MnOx-Biochar was produced by dipping corn cob biochar in 40 mM manganese sulfate followed by pyrolyzed at 600°C. The surface area, pore volume, pore size, and pH value at the zero-point charge of MnOx-Biochar were 130 m2/g, 0.044 cm3/g, 1.02 nm, and 7.05, respectively. From the FTIR spectrogram, a peak assignable to Mn-O was observed. The results showed that the initial pH of the wastewater did not affect the treatment efficiency. The optimum MnOx-Biochar dosage was 2 g/L. Equilibrium was reached within 120 min of reaction. During the first 15 min, the treatment rate constants (k) of the WW-A and WW-B treatment were 0.0647 min-1 and 0.0349 min-1, respectively. After 15 min, the k values of the WW-A and WW-B treatments were reduced to 0.0242 min-1 and 0.0094 min-1, respectively. The overall treatment efficiencies of the low COD wastewater (WW-A) and high COD wastewater (WW-B) were 97% and 78%, respectively. The treatment mechanisms involved both adsorption and oxidation. The adsorption efficiencies of the WW-A and WW-B treatments were 36% and 18%, respectively.
Keywords: Water Quality Monitoring and Analysis